PENGARUH VARIASI JENIS DAN KONSENTRASI ZAT FIKSASI PADA EKSTRAK DAUN PEPAYA SEBAGAI PEWARNA ALAMI PADA KAIN BATIK - Anisa Nur Fadhila; Tri Widayatno; Agus Haerudin (Universitas Mercu Buana, 2022)
One of the symbols that reflect Indonesian culture is batik. One of the processes of making batik is coloring. The use of traditional dyes is gradually being replaced by chemical dyes. However, chemical dyes can cause some environmental problems. To minimize the impact of environmental pollution, it is possible to reuse natural dyes. Papaya leaves were chosen because they can be used to produce non-food natural dyes by way of processing that is easier and more effective and is available in relatively large quantities. The chlorophyll content in papaya leaves is 13.91 mg/L after spinach leaves, kale leaves, and cassava leaves. Fixation agent is needed in the coloring process in order to suppress the color direction by changing the color intensity according to the type of mordant and variations in its concentration. This study used variations of alum and tunjung with concentrations of (35, 70, and 105) grams. The color quality is proven through the fabric color space test and the color fastness test to dry ironing heat and washing soap. The stages in this study were starting from material preparation, papaya leaf extraction, coloring, fixation, pelorodan, and testing the color space and color fastness. Based on the data obtained, it was concluded that the type and concentration of the optimal fixation agent in papaya leaf extract as a natural dye was the type of fixative agent of tunjung with a concentration of 105 grams.